Brain‐selective mild hypothermia promotes long‐term white matter integrity after ischemic stroke in mice. (16th September 2018) - Liu, Li‐Qiang; Liu, Xiang‐Rong; Zhao, Jing‐Yan; Yan, Feng; Wang, Rong‐Liang; Wen, Shao‐Hong; Wang, Lei; Luo, Yu‐Min; Ji, Xun‐Ming
Summary: Introduction: The neuroprotective effects of hypothermia in acute ischemic stroke are well documented. However, the mechanisms involved in the effects remain to be clearly elucidated and the role of hypothermia on long‐term white matter integrity after acute ischemic stroke has yet to be investigated. Aims: To investigate the role of mild focal hypothermia on long‐term white matter (WM) integrity after transient cerebral ischemia. Results: Mild focal hypothermia treatment immediately after ischemic stroke significantly promotes WM integrity 28 days after the occlusion of the middle cerebral artery (MCAO) in mice. Higher integrity of white matter, lower activation of total microglia, less infarct volume, and better neurobehavioral function were detected in hypothermia‐treated mice compared to normothermia‐treated mice. Furthermore, we found that hypothermia could decrease detrimental M1 phenotype microglia and promote healthy M2 phenotype microglia. In vitro, results also indicated that hypothermia promoted oligodendrocytes differentiation and maturation after oxygen glucose deprivation. Conclusion: Hypothermia promotes long‐term WM integrity and inhibits neuroinflammation in a mouse model of ischemic brain injury.